ANALISIS VALIDITAS DAN RELIABILITAS TES LITERASI SAINS INTEGRASI LINGKUNGAN DENGAN RASCH MODEL - Adhari, Desi; Santiani, Santiani; Fatmawati, Sri (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This study aims to create an integrated assessment instrument for environmental science literacy focused on thermodynamics for high school students. The research methodology employed is Research and Development (R&D), specifically using the 4-D model. Participants in the study included 34 twelfth-grade students from Public High School 1 Palangka Raya. The validity of the instrument was evaluated using Aiken's index with input from five expert validators, while its quality was analyzed through the Rasch Model. The findings indicate that the instrument demonstrates unidimensionality, with a Raw Variance Explained by Measures value of 43.2%, confirming its effectiveness in assessing the desired aspects of science literacy. Out of the 16 items analyzed, 13 were considered fitting. The instrument also showed exceptionally high reliability, boasting a Cronbach's Alpha value of 0.89, and most items exhibited no gender bias, according to the Differential Item Functioning (DIF) test. This instrument's development is anticipated to assist students in connecting scientific concepts to real-world scenarios, enhance their science literacy skills, and raise awareness of the importance of environmental conservation, particularly regarding peatland preservation in Palangka Raya.